2003
DOI: 10.1021/jp034231e
|View full text |Cite
|
Sign up to set email alerts
|

Solute Rotation and Solvation Dynamics in a Room-Temperature Ionic Liquid

Abstract: Steady-state spectra, rotation times, and time-resolved emission spectra of the probe 4-aminophthalimide (4-AP) in the ionic liquid 1-n-butyl-3-methylimidazolium hexafluorophosphate ([bmim+][PF6 -]) were measured over the temperature range 298−355 K. The steady-state spectroscopy indicates that the solvation energetics of 4-AP in [bmim+][PF6 -] are comparable to those of 4-AP in highly polar but aprotic solvents such as dimethylformamide and acetonitrile (π* ∼ 0.8, ∼ 0.4). The rotation of 4-AP in [bmim+][PF6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
341
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(371 citation statements)
references
References 54 publications
(128 reference statements)
28
341
2
Order By: Relevance
“…33,34 Experimental studies on the rotational motion of small molecules dissolved in ILs have also been reported. [35][36][37][38][39] We calculated  2 in Eq. 7 by using the measured viscosity data and assuming V of the van der Waals volumes of the cations in Table 3.…”
Section: Cation Molecular Motionmentioning
confidence: 99%
“…33,34 Experimental studies on the rotational motion of small molecules dissolved in ILs have also been reported. [35][36][37][38][39] We calculated  2 in Eq. 7 by using the measured viscosity data and assuming V of the van der Waals volumes of the cations in Table 3.…”
Section: Cation Molecular Motionmentioning
confidence: 99%
“…Previous fluorescence studies of orientational relaxation of RTILs have seen Debye-Stokes-Einstein (DSE) behavior 14 and possibly deviations from DSE behavior. [15][16][17] Most of the studies examined very polar and charged dye molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The 4-aminophthalimide molecule (4-AP, Figures 1 and 2) and its N-methyl derivative (NM-4-AP) have been widely used as fluorescence probes in investigations of the properties of many complex systems such as mixtures of solvents, [1] micelles, [2][3][4] cyclodextrines, [5] ionic liquids [6,7] and others. [8][9][10][11] The usefulness of 4-AP and NM-4-AP as probes is related to the strong dependence of their fluorescence maxima (n F max ), their quantum yields of fluorescence (f F ) and their fluorescence decay times (t F ) on the properties of their environment.…”
Section: Introductionmentioning
confidence: 99%